Assessment of the Severity of Paravalvular Regurgitation and its Role on Survival After Transcatheter Aortic Valve Replacement. Issue 1 (2nd January 2019) - Sannino, Anna; Stoler, Robert C.; Vallabhan, Ravi; Potluri, Srinivasa; Pollock, Benjamin; Filardo, Giovanni; Mack, Michael J.; Grayburn, Paul A.
ABSTRACT: Background: To evaluate the impact of various measurements of paravalvular regurgitation (PVR) on survival after transcatheter aortic valve replacement (TAVR). PVR can be difficult to grade and both its incidence and impact on survival may be decreasing as TAVR evolves. Methods: This retrospective study included 911 patients undergoing TAVR in two institutions. PVR was graded according to the 3-grade scheme proposed by the guidelines (PVR grade), and subsequently grade 2 and 3, and grade 0 and 1 were lumped together. PVR was also graded as a composite score (PVR score), based on 6 commonly used metrics. PVR grade, PVR score and its six individual components were tested against the risk of both 1-year and longer term mortality after TAVR. Results: Patients with moderate/severe PVR had a higher Society of Thoracic Sugeons (STS) score, higher levels of serum creatinine and larger left atria compared to patients with none/mild PVR. Moderate/severe PVR was more frequent with self-expandable and larger valves. After adjusting for American College of Cardiology (ACC) TAVR risk score, neither PVR grade, PVR score nor its six components were associated with an increased risk of mortality at 1-year (severe PVR adjusted HR: 0.75, 95% Confidence Interval [CI]: 0.19, 3.01, p = 0.50). However, intervention for clinically severe PVR increased the risk of mortality by more than 7-fold (adjusted hazard ratio [HR]: 7.6, 95% CI: 2.4, 23.5, p < 0.0001). Conclusions: In the contemporary era, moderate-severe PVR is uncommon. However, re-intervention for PVR portends a poor prognosis. This highlights the crucial importance of clinical judgment over imaging alone.